Relationship of Total Phenolic Content and Total Flavonoid Content Affecting Antioxidant Activity of Momordica subangulata Bl. and Lepionurus sylvestris Bl. ความสัมพันธ์ของปริมาณฟีนอลิกรวมและปริมาณฟลาโวนอยด์รวม ที่มีต่อฤทธิ์ต้านอนุมูลอิสระของแหมะและหมากหมก - ไชยธาดา ประกิต (Wichcha Journal Nakhon Si Thammarat Rajabhat University, 2019)
This research is aimed to study the relationship of total phenolic content and total flavonoids content with antioxidant activity of Momordica subangulata Bl. and Lepionurus sylvestris Bl. Leave and fruit of M. subangulata and L. sylvestris were extracted by Soxhlet extractor using ethyl acetate, acetone and ethanol as solvents. The investigation of the total phenolic content was analyzed by Folin-Ciocalteau’s reagent using gallic acid as a standard substance, total flavonoids content using quercetin as a standard substance, and antioxidant activity by 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. The results showed that the acetone extract of leaves of M. subangulata (MSLA) had the most of total phenolic content (150.12±5.41 mgGAE/g extract). The ethanol extract of fruit of L. sylvestris (LSFE) showed the highest of total flavonoids content (0.27±0.00 mgQE/g extract). The antioxidant activity was determined and its result showed that the acetone extract of leaves from M. subangulata (MSLA) showed the strongest antioxidant activity with IC50 of 37.47±8.18 mg/L, followed by the ethyl acetate extract of fruit from L. sylvestris (LSFA, 38.53±1.51 mg/L) and the ethanol extract of fruit from L. sylvestris Bl. (LSFE, 48.17±3.41 mg/L), respectively. The study of relationship between total phenolic content and total flavonoids content with antioxidant activity found that both the total phenolic and total flavonoid contents were negatively correlated with the 50% free radical inhibitory concentration. The total phenolic content had slightly more related than the total flavonoid content with Pearson’s correlation coefficient of -0.779 and -0.755, respectively.